O que dizem os egressos sobre a formação matemática no curso de Licenciatura Integrada em Educação em Ciências, Matemática e Linguagens da UFPA - MESCOUTO, Amanda Ketlen Barroso (2020)
The research investigated the teacher’s perception of the Integrated graduation in Sciences, Mathematics and Languages about the mathematical training obtained in the course. And analyzed the curricular matrix of the course, verifying the occurrence of mathematical contents of Primary Education I, directed to the learning of the future teachers. It had as guiding question: what the graduates of the Integrated Degree have to say about the mathematical formation in the course? The themes addressed to the mathematical formation of the future teachers bring in their menu the emphasis on "what to teach" and "how to teach"? The study was based on Shulman (2014) and other authors dealing with mathematical education and training. Was analyzed of the Course Pedagogical Project, the menus and a questionnaire directed to the graduates on the regular period, from 2010 to 2014. It is possible to be verified even being a new course, has a speech of innovation in classroom, it still makes the same mistakes as another teacher training courses for initial years, in other words, the lack of specific mathematical content that will be worked during practice, this is justified both by the themes bringing up general subjects as well as in the speeches of the respondents, expressing their perceptions about the mathematical formation received in the course, for example when they express the blocks of contents related to Elementary School I were not all worked, as well as there is a need for bigger and better approaches of mathematical subjects and of their practices for the strengthening of mathematical training in the course.